Therese Mound: a case study of coral bank development in the Belgica Mound Province, Porcupine Seabight - De Mol, Ben; Kozachenko, M; Wheeler, Andy; Alvares, Hugo; Henriet, Jean-pierre; Olu, Karine (International Journal of Earth Sciences, 2007)
High-resolution seismic profiles, swath bathymetry, side-scan sonar data and video imageries are analysed in this detailed study of five carbonate mounds from the Belgica mound province with special emphasis on the well-surveyed Therese Mound. The selected mounds are located in the deepest part of the Belgica mound province at water depths of 950 m. Seismic data illustrate that the underlying geology is characterised by drift sedimentation in a general northerly flowing current regime. Sigmoidal sediment bodies create local slope breaks on the most recent local erosional surface, which act as the mound base. No preferential mound substratum is observed, neither is there any indication for deep geological controls on coral bank development. Seismic evidence suggests that the start-up of the coral bank development was shortly after a major erosional event of Late Pliocene-Quaternary age. The coral bank geometry has been clearly affected by the local topography of this erosional base and the prevailing current regime. The summits of the coral banks are relatively flat and the flanks are steepest on their upper slopes. Deposition of the encased drift sequence has been influenced by the coral bank topography. Sediment waves are formed besides the coral banks and are the most pronounced bedforms. These seabed structures are probably induced by bottom current up to 1 m/s. Large sediment waves are colonised by living corals and might represent the initial phase of coral bank development. The biological facies distribution of the coral banks illustrate a living coral cap on the summit and upper slope and a decline of living coral populations toward the lower flanks. The data suggest that the development of the coral banks in this area is clearly an interaction between biological growth processes and drift deposition both influenced by the local topography and current regime.